Effect of Olive Oil and Almond Oil Ratios on the Physicochemical and Sensory Characteristics of Aromatherapy Massage Oil - chennia Ofta Fianes; Nur Ermawati (Universitas Duta Bangsa Surakarta, 2026)
Background: Aromatherapy massage oil is a topical preparation in which carrier oil selection critically determines physicochemical performance and sensory acceptance. Studies evaluating olive oil and almond oil combinations as carrier oils in multi-essential oil aromatherapy systems remain limited. Aim: This study aimed to evaluate the effect of different olive oil (Olea europaea) and almond oil (Prunus amygdalus) ratios on the physicochemical characteristics, stability, sensory properties, and skin safety of aromatherapy massage oil containing lavender (Lavandula angustifolia), citronella (Cymbopogon nardus), and chamomile (Matricaria recutita) essential oils. Methods: Three formulations were prepared using a Completely Randomized Design (CRD) with two replications: F1 (50:5 mL), F2 (5:50 mL), and F3 (27.5:27.5 mL). Evaluations included organoleptic characteristics, pH, viscosity, specific gravity, 28-day stability, hedonic test (30 panelists), and skin irritation test (closed patch test, 10 volunteers, 8 hours), analyzed using one-way ANOVA and repeated-measures ANOVA with post-hoc Tukey HSD (? = 0.05, SPSS v.23.0). Results: All formulations were stable over 28 days with consistent organoleptic properties and pH 5.00. Viscosity ranged from 4.106 ± 0.004 cP (F1) to 4.321 ± 0.004 cP (F3), all within 2.3-6.0 cP. Statistically significant viscosity changes were observed (p < 0.05) but were not practically meaningful. No significant difference in sensory preference was found (p = 0.825), with F3 descriptively obtaining the highest score (12.233). All formulations were non-irritating (ICDRG score 0). Conclusion: Carrier oil ratio variation influenced viscosity and specific gravity but not organoleptic stability, pH, or sensory acceptance. F3 was selected as the most optimal formulation based on combined viscosity profile, stability, and descriptive sensory preference. Limitations include short stability duration, absence of microbiological testing, and use of pH indicator paper in an oil-based system.